Políticas identitárias e de conjugalidades : agenciamentos na Galeria LGBTT do Presídio Central de Porto Alegre - Silva, Gabriela Baptista (2017)
The purpose of this study is to understand the identity and conjugal policies in an exclusive wing for transvestites, transgender, gays and bisexuals in the Central Prison of Porto Alegre. The data collection of this research was done through individual interviews and records of collective interventions in field diaries. The assumptions of the Grounded Theory and, as an analytical proposal, the conceptions derived from the American black feminism from the intersectional perspective are used as methodological dimension. Through this theoretical contribution is proposed an understanding of the strategic forms of agency in the prison territory engendered by persons in detention in this gallery. In addition to addressing the policies of conjugality, it is sought to reflect on the ways of experiencing sexuality and gender in the prison context from a dialogical identity perspective.